HUBUNGAN KECERDASAN EMOSIONAL DENGAN AKHLAK SISWA - Hilmiyyah, Azizah; Priatna, Oking Setia; Hamdani, Ikhwan (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine the relationship between emotional intelligence and the morals of students in MAN 1 Bogor City. This type of research is quantitative research. The population in this study were students of class XI MAN 1 Bogor City with a total of 353 students. The research sample was taken 15% of the total number of students in class XI, namely 52.95 rounded to 53 students. Data collection techniques used were observation, questionnaires and documentation, then the data that had been obtained were analyzed by normality test and product moment correlation test. using SPSS 25. The results obtained are based on the sig (2-tailed) value of 0.000 <0.05, which means that there is a significant relationship between emotional intelligence and student morals, besides that, it can be seen from the calculation of the Pearson correlation of 0.743. , and obtained that is 0.743 is in the interval 0.70-0.90, meaning that there is a strong relationship between emotional intelligence and morals.